3D Seismic Investigation of a Gas Hydrate and Fluid Flow System on an Active Mid‐Ocean Ridge; Svyatogor Ridge, Fram Strait - Waghorn, Kate Alyse; Bünz, Stefan; Plaza-Faverola, Andreia; Johnson, Joel E. (Geochemistry, Geophysics, Geosystems, 2018)
Accepted manuscript version. Published version available at https://doi.org/10.1029/2018GC007482 . Tectonic settings play a large role in the development of fluid flow pathways for gas migrating through sedimentary strata. Many gas hydrate systems worldwide are located on either passive continental margins, in large contourite deposits on the slopes of passive continental margins or on subduction margins. The Svyatogor Ridge, however, located at the northwestern flank of the Knipovich Ridge and south of the Molloy Transform Fault (Fram Strait), is a gas hydrate system which is located on an actively spreading margin. Svyatogor Ridge has evidence of shallow gas accumulations; a strong BSR indicating a gas hydrate and underlying free gas system, and fluid flow pathways to the seafloor culminating in pockmarks. Using a high‐resolution P‐Cable 3D seismic survey, we investigate how tectonic and sedimentary regimes have influenced the formation of this well‐developed gas hydrate system. Large‐scale basement faults identified in the seismic data are interpreted as detachment faults, which have exhumed relatively young ultramafic rocks. These detachment faults act as conduits for fluid flow, and are responsible for the formation of folds in the overlying sediments that are breached by faults. We propose a model for fluid flow within this system whereby as sedimentary faults breach upwards through the sedimentary strata, fluid is able to migrate further upwards. We find that the tectonic regime on Svyatogor Ridge is the dominant driver of fluid migration and episodic release at the seafloor.